Effects of CoAl precipitates on deformation behavior of Fe-Al-Co single crystals. (December 2017) - Yasuda, Hiroyuki Y.; Odawara, Yoshiaki; Soma, Kentaro; Yoshimoto, Takashi; Cho, Ken
Abstract: Effects of the CoAl precipitates with the B2 structure on the deformation behavior of Fe- x Al- x Co (at.%) single crystals ( x  = 15, 18, 20) were examined focusing on loading axis, precipitate morphology and deformation temperature. Strong precipitation hardening occurred owing to the precipitation of the CoAl phase in the bcc matrix, and not only <111> slip but <001> slip took place, which resulted from the difference in primary slip systems between the bcc matrix and the CoAl precipitates. It is also noted that the activated slip system depended strongly on the size and volume fraction of the CoAl precipitates. For instance, the primary slip direction at x  = 18 changed with increasing precipitate size in the following order: <111>, <001> and <111>. Higher volume fraction of the CoAl precipitates at higher x was favorable for the activation of <001> slip. The activated slip system also varied with deformation temperature, associated with the temperature dependence of the critical resolved shear stress of <111> and <001> slips. Graphical abstract: Highlights: Fe-Al-Co single crystals containing the CoAl precipitates exhibit strong hardening. Primary slip systems of the matrix and precipitates influence the hardening. <001> slip as well as <111> slip occurs depending on the loading axis. The hardening mechanism varies with the size and volume fraction of the precipitates. The activated slip system depends strongly on the deformation temperature.